The Impact of Information Presentation Formats and Types on Decision Performance: An Experimental Study of Cost-Based Decision Making - DYAH EKAARI SEKAR JATININGSIH; Mahfud Sholihin (The Indonesian Journal of Accounting Research, 2013)
This study examines the impact of cost information presentation formats and types on decision performance using an experimental method.  Using a customer profitability report generated from activity-based costing presented in tabular or graphical format and digital or manual type, subjects in this experiment have the task to determine price, which can influence company profitability. The design used in the experiment is 2X2X2 between subjects, with 60 managers in a food manufacturing industry as participants.  The results show that information presented digitally or manually in the format of tabular or graphical has significant impact for decision makers and lead to different profit performance.  Further analysis also shows that decision maker's nature of work has an impact on decision making process instead of knowledge.